Comparison of pharmacologic therapies alone versus operative techniques in combination with pharmacologic therapies for postoperative analgesia in patients undergoing laparoscopic cholecystectomy: A randomized controlled trial. (August 2022) - Kim, Hyun-Chang; Song, Young; Lee, Jong Seok; Jeong, Myeong Eun; Lee, Yongmin; Lim, Jin Hong; Kim, Do-Hyeong
Abstract: Background: Laparoscopic cholecystectomy (LC) causes moderate pain. Various operative analgesic techniques and pharmacologic treatments can reduce postoperative pain. This single-center, single-surgeon randomized controlled study aimed to assess the efficacy of combined operative analgesic techniques and pharmacologic analgesia in decreasing pain in patients undergoing LC. Materials and methods: Fifty-nine patients scheduled for LC were assigned into two groups. In the pharmacologic analgesia (P) group (n = 29), patients were treated with pharmacologic intervention, including preoperative celecoxib (200 mg), intraoperative acetaminophen (1 g), and dexamethasone (8 mg). In the operative analgesic treatments with pharmacologic analgesia (OP) group (n = 30), patients were treated with both operative analgesic techniques and pharmacologic analgesia, including low-pressure pneumoperitoneum, intraperitoneal normal saline irrigation, and aspiration of intraperitoneal carbon dioxide. The area under the curve (AUC) of pain score for postoperative 24 h was assessed at 0, 2, 6, and 24 h post-operation. The analgesic requirements and sleep quality at postoperative day 1 were assessed. Results: The AUC/24 h of pain scores at rest and on cough were lower in the OP group (p < 0.001 and p = 0.001, respectively). The pain scores at rest were lower in the OP group at postoperative 2, 6, and 24 h (p = 0.001, p = 0.001, and p = 0.048, respectively). The pain scores on cough were lower in the OP group at postoperative 2 and 6 h (p = 0.004 and p = 0.008, respectively). Analgesic requirements were comparable. The sleep quality score at postoperative day 1 was higher in the OP group (56 ± 18 vs. 67 ± 15, absolute difference, 10; 95% confidence interval, 2 to 19; p = 0.017). Conclusions: Combined operative analgesic therapies and pharmacologic analgesia compared to pharmacologic analgesia alone decreased pain scores and increased sleep quality in patients undergoing LC. Highlights: Combined pharmacologic and surgical maneuver analgesia decrease pain following laparoscopic cholecystectomy. Surgical maneuver analgesia included low pressure pneumoperitoneum, saline irrigation, carbon dioxide aspiration. These also increased sleep quality in patients following laparoscopic cholecystectomy. This treatment can be considered instead of treatment with pharmacologic analgesia alone in laparoscopic cholecystectomy. Combined pharmacologic and surgical maneuver analgesia needs to be tested in a larger, multicenter cohort.